Places database - Palmer, John (The University of Hull, 2008)
A database of the place-names recorded in Domesday Book based upon the original indexes to the printed Phillimore edition (1975-86) edited by John Morris, subsequently published by Phillimore as a national index edited by John Palmer and J. McN. Dodgson (1992) and later included in the edition of Domesday Explorer published by Phillimore in 2000, edited by John Palmer, Matthew Palmer and George Slater. This edition incorporates revisions to the place-names and their Ordnance Survey coordinates by Frank Thorn